Trust, Endangerment, and Divine Vulnerability: An Interdisciplinary Conversation with Niklas Luhmann and K.E. Løgstrup. Issue 4 (4th December 2017) - Christoffersen, Mikkel Gabriel
Abstract: Faith is trusting God in the midst of endangerment. Yet, human experience of excessive suffering has challenged any spontaneous trust in God. In this article, I reconsider the idea of faith as trust in God, adding an emphasis on the divine vulnerability in the incarnation. I develop a more complex view of trust inspired by the Danish philosopher of religion K.E. Løgstrup and the German sociologist Niklas Luhmann. I use this view of trust to reconsider the relationship between trust and faith in the God of incarnation.